Tanggung Gugat Pelaku Usaha Dalam Praktik Jual Beli Myteri Box Yang Cacat Produk Melalui Vending Machine - Meirza Aulia Chairani; Trinah Asi Islami (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
Abstract-The purpose of this study is to determine the responsibility of business actors who sell defective Mystery Boxes sold at Vending Machines.The type of research used in this legal research is Normative Juridical Research. Statute approach and conceptual approach. Using primary and secondary legal sources. Buying and selling Mystery Boxes through Vending Machines violates Article 4 letters b and c of the PK Law, consumers have the right to choose goods and get services in accordance with the promised exchange rate and guarantee conditions, and provide correct and honest information about the condition and guarantee of the goods. Business actors are obliged to compensate for goods sold Article 7 Letters f and g of the PK Law. Sanctions for business actors for product defects of Mystery Boxes through Vending Machines in accordance with Article 11 letter c of the PK Law are prohibited from deceiving/misleading consumers and not intending to sell the goods offered but with the intention of selling other goods. The consequences of getting sanctions in accordance with Article 62 paragraph (2) of the PK Law are resolved by litigation and non-litigation submitted by consumers in dispute resolution.